2009
DOI: 10.3748/wjg.15.1809
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil consumption and non-alcoholic fatty liver disease

Abstract: The clinical implications of non-alcoholic fatty liver diseases (NAFLD) derive from their potential to progress to fibrosis and cirrhosis. Inappropriate dietary fat intake, excessive intake of soft drinks, insulin resistance and increased oxidative stress results in increased free fatty acid delivery to the liver and increased hepatic triglyceride (TG) accumulation. An olive oil-rich diet decreases accumulation of TGs in the liver, improves postprandial TGs, glucose and glucagonlike peptide-1 responses in insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(98 citation statements)
references
References 80 publications
3
87
0
5
Order By: Relevance
“…Epidemiologic information demonstrates that the pathogenesis of fatty liver is related to high circulating cholesterol (Lankarani et al, 2013). The risk factors comprise of high fat and protein diet, male gender, the presence of metabolic syndrome characteristics, extra meals before sleep, and sedentary lifestyle.Although the mechanism is complex and poorly understood, it is believed to involve an imbalance of fatty acid metabolism that leads to hepatic triglyceride accumulation (Shi et al,2012).It is an important progressing liver damage and the high incidence of fatty liver indicated that there is a need for the new management of fatty liver and its related diseases (Gu et al,.2007;Assy et al,2009;Tsuruta et al,2011). The fatty liver can also lead to fibrotic change and cirrhosis, which have no potential drugs for the treatment (Zelber-Sagi,et al, 2011;Li et al,2010;Luper et al,1998).…”
mentioning
confidence: 99%
“…Epidemiologic information demonstrates that the pathogenesis of fatty liver is related to high circulating cholesterol (Lankarani et al, 2013). The risk factors comprise of high fat and protein diet, male gender, the presence of metabolic syndrome characteristics, extra meals before sleep, and sedentary lifestyle.Although the mechanism is complex and poorly understood, it is believed to involve an imbalance of fatty acid metabolism that leads to hepatic triglyceride accumulation (Shi et al,2012).It is an important progressing liver damage and the high incidence of fatty liver indicated that there is a need for the new management of fatty liver and its related diseases (Gu et al,.2007;Assy et al,2009;Tsuruta et al,2011). The fatty liver can also lead to fibrotic change and cirrhosis, which have no potential drugs for the treatment (Zelber-Sagi,et al, 2011;Li et al,2010;Luper et al,1998).…”
mentioning
confidence: 99%
“…These cytokines trigger several signal transduction pathways, for example the serine/threonine kinases [protein kinase-C (PKC)], c-JUN NH2-terminal kinase-1 (JNK), and kappa B-kinase inhibitor, causing hepatic IR [6] . The PKC binds to the insulin receptor, inhibits its tyrosine kinase activity and interfere with the ability of insulin to phosphorylate the insulin receptor substrate-2 [18,19] . Furthermore, abundant dietary fat consumption increases FFAs delivered to the liver.…”
Section: The Role Of Diet In the Development Of Nafldmentioning
confidence: 99%
“…Once the diagnosis of NAFLD was made, the first step will be a lifestyle intervention using a combination of diet, active walking, and behavior modification [118], with a goal of >10% weight reduction [119]. Mediterranean diet derived mainly from olive oil (rich in omega-9) is recommended [120,121]. We advise to reduce or discontinue the consumption of fast foods and regular soft drinks, which contain fructose [122].…”
Section: Discussionmentioning
confidence: 99%